Doenitin-1: A novel Kunitz family protein with versatile functions during feeding and reproduction of the tick Haemaphysalis doenitzi - Lu, Jialin; Wang, Kuang; Gao, Zhihua; Zhang, Songbo; Li, Hao; Shi, Yanqing; Song, Xuecheng; Liu, Jingze; Yu, Zhijun; Yang, Xiaolong (Frontiers in Veterinary Science, 2022)
As obligate blood-feeding ectoparasites, ticks secrete a great diversity of antithrombin molecules during feeding. In the present study, a novel antithrombin gene, named as Doenitin-1, was characterized from the tick Haemaphysalis doenitzi. It has an open reading frame size of 426 bp, which encoding 141 amino acids with the predicted molecular weight of 15.8 kDa. Fibrinogen coagulation test showed that the coagulation time increased significantly with the increase of rDoenitin-1 protein concentration, and the activated partial thromboplastin time (APTT) and prothrombin time (PT) assays showed that rDoenitin-1 significantly prolonged the coagulation time of APTT, indicating that rDoenitin-1 has anticoagulant activity in vitro. In addition, the rDoenitin-1 present inhibitory activity on thrombin and cathepsin G. The hemolysis rate of rDoenitin-1 on healthy human blood cells was 4.25%, and no obvious hemolysis activity was observed. Comparison with other life stages shows that the higher expression occurs in adults, and tissue comparison indicated a higher expression in midguts. RNAi results indicated that interference of Doenitin-1 significantly reduced engorgement rate and egg hatchability of H. doenitzi, and the engorged body weight slightly reduced. In conclusion, these results suggested that novel gene Doenitin-1 function in blood-feeding of H. doenitzi, and perform various functions during feeding and reproduction of H. doenitzi. Doenitin-1 may be a potential vaccine candidate for tick control and for future developing new antithrombotic drugs.